SELF-EFFICACY AND PROACTIVE COPING IN ADOLESCENT SMOKING CESSATION: A CORRELATIONAL STUDY - Wini Hadiyani; Atika Nur Vicry (DPW PPNI Provinsi Jawa Barat, 2025)
Background: Adolescence is a critical developmental stage marked by emotional, social, and environmental challenges that may increase susceptibility to smoking. Many adolescents perceive smoking as a coping mechanism for stress and peer pressure. Psychological resources such as self-efficacy and proactive coping are considered important protective factors in smoking prevention and cessation. Objective: This study aimed to examine the association between self-efficacy and proactive coping in smoking cessation among adolescents. Methods: A quantitative correlational study with a cross-sectional design was conducted among 125 junior high school students aged 13–16 years in West Java, Indonesia. Participants were selected using proportional and simple random sampling techniques. Data were collected using the Smoking Self-Efficacy Questionnaire-12 and the Proactive Coping Smoking Cessation questionnaire. Statistical analysis was performed using the Spearman rank correlation test with a significance level set at 0.05. Results: The findings showed that most participants demonstrated high levels of self-efficacy (78.4%) and proactive coping (68.8%). A significant positive correlation was identified between self-efficacy and proactive coping (r = 0.548; p < 0.05), indicating that adolescents with stronger confidence in resisting smoking were more likely to engage in proactive coping behaviors, such as avoiding high-risk situations and seeking social support. Conclusion: Self-efficacy is positively associated with proactive coping in adolescent smoking cessation. Strengthening both psychological confidence and adaptive coping skills should be prioritized in adolescent smoking prevention and cessation programs.